PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. JNE EXPRESS CABANG CIKUPA - Roynaldy Adi Saputra; Kenny Astria (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of leadership style and work discipline on employee performance at PT. JNE Express Cikupa Branch. The type of research used is quantitative research. The population was taken from all employees, namely 60 people, Quantitative method using saturated sample technique. Data analysis uses data instrument tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Data analysis uses data instrument tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Leadership style and work discipline have a positive and significant effect on employee performance with the regression equation Y = 20.543+0.334X1+0.357X2. These results show that the correlation coefficient is 0.628. With the calculated F value > F table, namely 18.545 > 3.160 with a significance level of 0.000 < 0.005. Meanwhile, leadership style on employee performance with a calculated T value > T table is 4.448 > 2.001 with a significant value of 0.000 < 0.005. Then work discipline with a calculated T value > T table, namely 5.204 > 2.001 with a significant value of 0.000 < 0.005. So it can be concluded that leadership style and work discipline have a positive and significant influence on employee performance